Uncover of the motivation of new students to choose the Indonesia language education study program - Andriani, Margareta; Agustian, Muhammad (Edelweiss Applied Science and Technology, 2025)
This study aims to explore the reasons why new students choose the Indonesian Language Education Study Program in the modern era and understand their goals after graduation. The research employs a qualitative method with a descriptive approach. Data were collected through interviews and questionnaires consisting of 10 questions related to intrinsic and extrinsic motivation. A total of 13 new students were the subjects of the research, with a total of 65 answers analyzed. The results of the study showed that intrinsic motivation was the dominant factor in students’ decisions to choose this study program, with 56 or 80.14% of the answers being "yes" from the total intrinsic motivation questions. In contrast, extrinsic motivation only accounted for 19 or 29.24% of "yes" answers. Based on the interviews, all subjects stated that their main goal after graduation was to become a teacher or teaching staff. These findings suggest that personal interests, love for education, and aspirations to become educators play an important role in student decisions. Extreme motivations, such as economic or social impulses, have less influence. This research provides insight for study program managers to design strategies that support student needs, especially in maximizing the potential of intrinsic motivation to enhance their academic and professional success.